Preparation and Characterization of Cellulose Triacetate as Support for Lecitase Ultra Immobilization - da Silva, Francielle Batista (Molecules, 2017)
The use of polymers as supports for enzyme immobilization is a strategy that enables to remove the enzymes from a chemical reaction and improve their efficiency in catalytic processes. In this work, cellulose triacetate (CTA) was used for physical adsorption of phospholipase Lecitase ultra (LU). CTA is more hydrophobic than cellulose, shows good performance in the lipases immobilization being a good candidate for immobilization of phospholipases. We investigated the immobilization of LU in CTA, the stability of the immobilized enzyme (CTA-LU) and the performance of CTA-LU using soybean oil as a substrate. LU was efficiently immobilized in CTA reaching 97.1% in 60 min of contact with an enzymatic activity of 975.8 U·g(−1). The CTA-LU system presents good thermal stability, being superior of the free enzyme and increase of the catalytic activity in the whole range of pH values. The difference observed for immobilized enzyme compared to free one occurs because of the interaction between the enzyme and the polymer, which stabilizes the enzyme. The CTA-LU system was used in the transesterification of soybean oil with methanol, with the production of fatty acid methyl esters. The results showed that CTA-LU is a promising system for enzymatic reactions.